Cysticercosis of Breast Mimicking Fibroadenoma: A Case Report - Rao .S, Anil Mohan (Journal of Neonatal Surgery, 2025)
Cysticercosis is a parasitic infestation which can affect various structures of human body .Clinicians and pathologists need to be aware of its unusual presentations to identify and detect it an earlier stage to differentiate from other conditions which can have similar clinical and pathological presentations.Various pathological techniques such as fnac[fine needle aspiration cytology] and biopsy can aid in diagnosis facilitated by serological, radiological techniques such as X -ray,ultrasonography ,CT /MRI Scan.The early and prompt diagnosis by proper clinical suspicion supplemented by pathological examination helps in the management of the condition.In this study we present a unusual and rare presentation of cysticercosis of breast